Seminoma and sertolioma in a male pseudohermaphrodite dog with unilateral cryptorchidism: short communication - Madureira, Renata; Reis Filho, Nazilton de Paula; Santos, Angélica Rossotti dos; Dias, Ana Lúcia; Headley, Selwyn Arlington; Mascarenhas, Nilva Maria Freres; Brum, Juliana Sperotto (Semina: Ciências Agrárias, 2017)
A male miniature Schnauzer with cryptorchidism and a mass growth in the right inguinal canal was admitted to the clinical center of a veterinary hospital. During surgical resection of the mass, tubular formations were found, connecting the mass to the left testicle. Histopathology revealed that the tubular formations were uterine tubes and the mass was a seminoma associated with a sertolioma of the right testicle. Further analysis also showed atrophy of the left testicle. Cytogenetic evaluation revealed normal chromosomes of male gender, 78, XY, which led to the conclusion that this was a male pseudohermaphrodite.